Functional characterisation of resistance gene orthologues in cassava using gene editing - Ramulifho, Elelwani (My University, 2021)
Cassava (Manihotesculenta, Crantz) is the 3rdlargest source of carbohydrates in Africa and feeds millions globally. Although cassava can strive in drought prone regions, no genotype has overcome the threat by the geminivirus South African cassava mosaic virus (SACMV), which causes cassava mosaic disease (CMD)and can lead to 82% cassava production losses. Cassava landrace TME3 shows tolerance to SACMV while T200 landrace is highly susceptible. Disease resistance genes (R genes) encoded NBS-LRR proteins are key players in host defence mechanisms because of their role as receptors that recognise pathogen effectors and trigger plant effector-triggered immunity (ETI). The first objective of this study was aimed to analyse the amino acid sequences of two NBS-LRR resistance gene analogs (RGAs) MeTNL and MeRPPL1, and to determine their putative role in tolerance or susceptibility to the South African cassava mosaic virusin planta, using virus induced gene silencing (VIGS) and transiently in protoplasts, using clustered regular interspaced short palindromic repeats-CRISPR-associated protein 9 (CRISPR-Cas9) genome editing technologies. Cassava mosaic disease-tolerant cassava landrace TME3 plantlets were inoculated with SACMV DNA A-derived VIGS vector and challenged with SACMV. Relative qPCR results demonstrated that the MeRPPL1and MeTNL-VIGS-silencing vectors decreased expression of MeRPPL1and MeTNL, respectively in TME3 compared to GFP-vector only control. This consequently led to increased SACMV DNA A accumulation in MeRPPL1 and MeTNL-silenced plants compared to SACMV infected plants not treated with the silencing vector. CRISPR-silencing vectors and SACMV were used to transfect TME3 protoplasts isolated from leaf mesophyll cells. In contrast to VIGS, CRISPR-Cas silencing vectors with/without SACMV co-infection resulted in increased expression of both MeRPPL1and MeTNL in TME3 protoplasts compared to the CRISPR-Cas vector only control. Furthermore, mutagenesis studies revealed that CRISPR-Cas vector and SACMV induced mutations randomly in MeRPPL1, resulting in total replacement of the highly conserved MHD motif of the MeRPPL1 translated polypeptide with other amino acids. This would abolish the regulatory role for the MHD motif in the control of R protein activity and could account for the increase in SACMV DNA A accumulation observed in MeRPPL1-silenced protoplasts. MeTNL could not be sequenced due to primers not binding to the target regions and no conclusions could be drawn as to the role of the resultant mutations from CRISPR-Cas silencing and SACMV transfections. Results have shown the involvement of the two R genes in TME3 tolerance and response to SACMV. The second objective of this study was aimed to identify the leaf proteome involved in anti-viral defence. Liquid chromatography mass spectrometry (LC-MS) identified 2682 (54 differentially expressed) and 2817 (206 differentially expressed) proteins in both landraces at systemic infection (32 dpi) and symptom recovery (67 dpi), respectively. KEGG and STRING analysis identified differences in DEPs between the two landraces, with metabolic pathways highly enriched at both timepoints, and defence-associated pathways such as the chloroplast, proteasome and ribosome enriched at the recovery stage (67 dpi) in TME3. At 67 dpi, a large number of over-expressed proteins (56%) in TME3 were localized in the chloroplast, whereas 31% of these chloroplast proteins were under-expressed in T200. A chloroplast protein (Manes.15G029400) was over-expressed in TME3 (1.25 ratio) at symptom recovery stage (67 dpi). The expression of the Arabidopsis homolog (AT4G14880) of this TME3 chloroplast protein is mediated by abscisic acid (ABA),which is synthesized in the chloroplast. We propose that chloroplast proteins and ABA-mediated defence mechanisms play a role in the reduction of SACMV virus replication and symptoms in TME3 at 67 dpi. RPT2 has been linked with PAMP triggered immunity (PTI) and effector triggered immunity (ETI). RPT proteins were associated with the reduction in systemic infection in TME3 landrace at 67 dpi. Regulatory particle triple-ATPase (RPT) subunits 2a/b of the 26S Proteasome complex were shown to directly interact with a Proteasome component family (Manes.01G032500) and a Holliday junction DNA helicase RuvB P-loop family (Manes.05G155000) that were under-expressed in TME3. In TME3 at recovery, a PCI (Proteasome, COP9 signalosome, and initiation factor 3) domain-containing protein (Manes.01G032500) was also under-expressed in TME3 compared to over-expression (7-fold ratio) in T200. These findings suggest that under-expression of proteasome associated components may contribute to SACMV tolerance in TME3. Sac52, also known as the ribosomal protein L10 (RPL10), was found to interact with Ribosomal_L7Ae domain-containing protein homolog (Manes.12G139100, AT1G77940),which was over-expressed uniquely in TME3 only at 67 dpi. Since L10 is a known key player in the NIK1-mediated antiviral immunity defence response to geminivirus infection triggering ETI, we propose that Sac52 is associated with the reduction in systemic infection in TME3 landrace. In conclusion, the differences in proteome responses between SACMV challenged susceptible and tolerant cassava landraces and these above-mentioned proteins warrant further investigation
A thesis submitted to the Faculty of Science, University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Molecular and Cell Biology, 2021